Effects of type of substrate and dilution rate on fermentation in serial rumen mixed cultures - Ungerfeld, Emilio M.; Cancino-Padilla, Nathaly; Vera-Aguilera, Nelson; Scorcione, M. Carolina; Saldivia, Marcelo; Lagos-Pailla, Lorena; Vera, Milena; Cerda, Cristián; Muñoz, Camila; Urrutia, Natalie; Martínez, Emilio D. (Frontiers in Microbiology, 2024)
Forages and concentrates have consistently distinct patterns of fermentation in the rumen, with forages producing more methane (CH4) per unit of digested organic matter (OM) and higher acetate to propionate ratio than concentrates. A mechanism based on the Monod function of microbial growth has been proposed to explain the distinct fermentation pattern of forages and concentrates, where greater dilution rates and lower pH associated with concentrate feeding increase dihydrogen (H2) concentration through increasing methanogens growth rate and decreasing methanogens theoretically maximal growth rate, respectively. Increased H2 concentration would in turn inhibit H2 production, decreasing methanogenesis, inhibit H2-producing pathways such as acetate production via pyruvate oxidative decarboxylation, and stimulate H2-incorporating pathways such as propionate production. We examined the hypothesis that equalizing dilution rates in serial rumen cultures would result in a similar fermentation profile of a high forage and a high concentrate substrate. Under a 2 × 3 factorial arrangement, a high forage and a high concentrate substrate were incubated at dilution rates of 0.14, 0.28, or 0.56 h−1 in eight transfers of serial rumen cultures. Each treatment was replicated thrice, and the experiment repeated in two different months. The high concentrate substrate accumulated considerably more H2 and formate and produced less CH4 than the high forage substrate. Methanogens were nearly washed-out with high concentrate and increased their initial numbers with high forage. The effect of dilution rate was minor in comparison to the effect of the type of substrate. Accumulation of H2 and formate with high concentrate inhibited acetate and probably H2 and formate production, and stimulated butyrate, rather than propionate, as an electron sink alternative to CH4. All three dilution rates are considered high and selected for rapidly growing bacteria. The archaeal community composition varied widely and inconsistently. Lactate accumulated with both substrates, likely favored by microbial growth kinetics rather than by H2 accumulation thermodynamically stimulating electron disposal from NADH into pyruvate reduction. In this study, the type of substrate had a major effect on rumen fermentation largely independent of dilution rate and pH.